Energy storage : a new approach - Zito, Ralph; Ardebili, Haleh (John Wiley & Sons, Inc. ; Scrivener Publishing LLC, 2019)
"This new revision of an instant classic presents practical solutions to the problem of energy storage on a massive scale. This problem is especially difficult for renewable energy technologies, such as wind and solar power, that, currently, can only be utilized while the wind is blowing or while the sun is shining. If energy storage on a large scale were possible, this would solve many of our society's problems. For example, power grids would not go down during peak usage. Power plants that run on natural gas, for example, would no longer burn natural gas during the off-hours, as what happens now. These are just two of society's huge problems that could be solved with this new technology. This new edition includes additional discussion and new sections on energy problem including increasing population and greenhouse effects, and an expanded overview of energy storage types. Chapter two has been expanded to provide further discussion of the fundamentals of energy and new sections on elastic, electrical, chemical, and thermal energy. Two new chapters have been added that provide a discussion of electrolytes and membranes and on flexible and stretchable energy storage devices. A new section has also been added on the future of energy storage in the final chapter. This is a potentially revolutionary book insofar as technical books can be "revolutionary." The technologies that are described have their roots in basic chemistry that engineers have been practicing for years, but this is all new material that could revolutionize the energy industry. Whether the power is generated from oil, natural gas, coal, solar, wind, or any of the other emerging sources, energy storage is something that the industry must learn and practice. With the world energy demand increasing, mostly due to the industrial growth in China and India, and with the West becoming increasingly more interested in fuel efficiency and "green" endeavors, energy storage is potentially a key technology in our energy future. In today's environment, technology is far behind society's energy needs. Wind and solar power are limited because energy from these sources cannot be harnessed when the wind isn't blowing or the sun isn't shining. Power plants can go down during peak hours, and natural resources, such as coal and natural gas, are wasted keeping power plants running at higher than peak capacity, to guard against going down due to unexpected high usage. If there were a technology that could harness energy and store it on a massive scale, like a huge battery, it would solve all of these problems. Power would be cheaper, more dependable, and society could utilize renewable sources much more than is the current practice"--